Local governments' financial vulnerability analysing the impact of the COVID-19 pandemic - Padovani, Emanuele; Scorsone, Eric A. (Eric Anthony); Iacuzzi, Silvia; Valle de Souza, Simone (London New York, NY Routledge, 2022)
Local Governments' Financial Vulnerability presents a conceptual framework developed to examine how vulnerable local finances were before and in the immediate aftermath of the Covid-19 pandemic crisis by mapping and systematising its dimensions and sources. The model is then applied to eight countries with different administrative models and traditions: Australia, Austria, Bosnia and Herzegovina, Germany, Italy, Portugal, Spain, and the USA. Comparative results reveal not only that Covid-19 impacts and policy tools had a lot of similarities across countries, but also that financial vulnerability has an inherently contingent nature in time and space and can lead to paradoxical outcomes. The book shows that the impact of the crisis on local governments' finances has been postponed and that financial vulnerability is expected to increase dramatically for a few years following the pandemic, especially in larger and richer municipalities which are traditionally more autonomous and less financially vulnerable. The authors provide timely insights and analytical tools that can be useful for both academic and public policy purposes, to further appreciate local governments' financial vulnerability, especially during crises. This book is a valuable resource for practitioners and academics, as well as students of public policy, public management, financial management, and public accounting. Local governments can use the framework to better appreciate and manage their financial vulnerability, while oversight authorities can use it to help local governments become less financially vulnerable or, at least, more aware of their financial vulnerability. Financial institutions, advisors, and rating agencies may use this publication to refine or revise their models of credit risk assessment"--
1. Introduction
Emanuele Padovani, Eric Scorsone, Silvia Iacuzzi and Simone Valle de Souza

2. Financial Vulnerability
Emanuele Padovani, Silvia Iacuzzi, Susana Jorge and Liliana Pimentel

3. Australia
Andrea Wallace and Brian Dollery

4. Austria
Robert Blöschl and Thomas Prorok

5. Bosnia and Herzegovina
Jelena Poljasevic

6. Germany
René Geissler

7. Italy
Emanuele Padovani and Silvia Iacuzzi

8. Portugal
Susana Jorge and Liliana Pimentel

9. Spain
Isabel Alijarde Brusca

10. United States of America
Mary Schulz, Eric Scorsone and Simone Valle de Souza

11. Conclusions
Emanuele Padovani, Simone Valle de Souza and Silvia Iacuzzi
Includes bibliographical references and index.
Keywords: Local government -- Finance; COVID-19 (Disease) -- Economic aspects; COVID-19 (Disease) -- Political aspects; Comparative government